Foreign investment promotion policy tools: monitoring and challenges in the recovery of the Ukrainian economy - Софіщенко, Ірина Ярославівна (Київський національний університет імені Тараса Шевченка, 2023)
Background. The purpose of the article is to develop proposals for improving the policy of foreign investment promotion under the conditions of recovery of the Ukrainian economy considering the peculiarities of the methods and mechanisms of using foreign investment promotion tools, generalizing the domestic experience of their application. The article critically summarizes the experience of developing the Ukrainian foreign investment promotion policy, which allows for determining the direction of its adaptation in modern conditions. Methods. A definition is provided for the concept of "policy to promote foreign investment". In accordance with the objectives of the study, monitoring of fiscal, financial, and administrative instruments is carried out, and the selection of methods and policy instruments is based on the author's approaches to their typology. Results. An assumption has been made that the recovery of Ukraine's economy based on the attraction of foreign investments needs to take into account the results of the previous domestic experience of using the tools of the investment promotion policy. The limitations of the use of fiscal policy instruments, which necessitate the coordination of the system of the country's economic policies, are determined. Defects in the practice of applying financial policy instruments are identified. The experience of reforming the system of administrative instruments is summarized. Based on the results of the research, the factors that lead to the formation of a new political cycle of determining priorities, goals, tasks, and designing policy measures for the promotion of foreign investments have been identified. Сonclusions. The article substantiates the importance of designing measures to influence the investment environment and investment activity based on a comprehensive and coordinated approach to the use of policy instruments, ensuring the balance of stakeholders' interests, taking into account changes in the external environment of policy formation, restrictions and challenges related to the current state of the economy.

Вступ. Стан середовища міжнародної і національної економіки формує масштабні виклики й актуалізує завдання визначення найбільш відповідних заходів інвестиційної політики для відновлення української економіки. Дослідження розглядає практику застосування комплексу інструментів державної політики сприяння іноземним інвестиціям в Україні. Методи. Застосовано інституційний і системний підхід для вивчення економічної політики як явища міжнародної економіки. Методи та інструменти політики досліджено на основі авторського підходу до їхньої типології, запропоновано уточнене визначення поняття «політика сприяння іноземним інвестиціям». Результати. Здійснено критичний аналіз практики реалізації вітчизняної політики сприяння іноземним інвестиціям. Сформовано припущення, що відновлення економіки України на основі залучення іноземних інвестицій потребує врахування попереднього вітчизняного досвіду використання інструментів політики стимулювання інвестицій з урахуванням нових викликів та завдань відновлення української економіки. Висновки. За результатами прикладного дослідження визначено важливість комплексного та узгодженого підходу до використання інструментарію політики з урахуванням змін у зовнішньому середовищі її формування.
Інструментарій політики сприяння іноземним інвестиціям: моніторинг та виклики в умовах відновлення української економіки
Keywords: foreign direct investment; promotion policy; fiscal incentives; financial incentives; deregulation; прямі іноземні інвестиції; політика сприяння прямих іноземних інвестицій (ПІІ); фіскальні стимули; дерегуляція; фінансові стимули